2011
DOI: 10.1186/1742-2094-8-177
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of spinal cord synaptic activity by tumor necrosis factor α in a model of peripheral neuropathy

Abstract: BackgroundThe cytokine tumor necrosis factor α (TNFα) is an established pain modulator in both the peripheral and central nervous systems. Modulation of nociceptive synaptic transmission in the spinal cord dorsal horn (DH) is thought to be involved in the development and maintenance of several pathological pain states. Increased levels of TNFα and its receptors (TNFR) in dorsal root ganglion (DRG) cells and in the spinal cord DH have been shown to play an essential role in neuropathic pain processing. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 61 publications
1
24
1
Order By: Relevance
“…TNF-α concentration in spinal cord dorsal horn are elevated in several neuropathological disorders associated with hyperalgesia 15, 16. In our study, rats with streptocotozin-induced diabetes had significantly elevated blood glucose levels, decreased body weights, and reduced pain threshold compared with control rats.…”
Section: Discussionsupporting
confidence: 51%
“…TNF-α concentration in spinal cord dorsal horn are elevated in several neuropathological disorders associated with hyperalgesia 15, 16. In our study, rats with streptocotozin-induced diabetes had significantly elevated blood glucose levels, decreased body weights, and reduced pain threshold compared with control rats.…”
Section: Discussionsupporting
confidence: 51%
“…Consistent with this high level of expression of TRPV1 channels, regulation (activation, desensitization and inhibition) of TRPV1 channels has a marked effect on glutamate release from these afferents (Spicarova et al, ). It has been suggested that modulation of TRPV1 channels in the dorsal horn could underlie several pathological pain states (Kanai et al, ; Spicarova et al, ; Spicarova et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Painful peripheral pathologies including tissue inflammation alter the expression and/or activity of both TRPV1 channels and CB 1 receptors (Richardson et al, ; Amaya et al, , ; Luo et al, ; Kanai et al, ; Spicarova and Palecek, ; Spicarova et al, ; Kwon et al, ). Inflammation also induces changes in anandamide levels in the spinal cord (Buczynski et al, ; Costa et al, ) and the expression of enzymes synthesizing and hydrolysing anandamide, in DRG neurons (Lever et al, ; Sousa‐Valente et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…66 were made to minimize animal suffering and to reduce the number of animals used. Acute spinal cord slices were prepared altogether from 15 juvenile male Wistar rats ∼ P21, as previously described (Spicarova et al 2011, Spicarova et al 2014a. The rats were deeply anesthetized (Forane ®, Abb Vie Czech Republic), lumbar spinal cords were removed and immersed in oxygenated ice-cold dissection solution containing (in mM): 95 NaCl, 1.8 KCl, 7 MgSO 4 , 0.5 CaCl 2 , 1.2 KH 2 PO 4 , 26 NaHCO 3 , 25 D-glucose, 50 sucrose.…”
Section: Introductionmentioning
confidence: 99%